2019
DOI: 10.1111/jcmm.14623
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin attenuates cell proliferation of uveal melanoma cells by inhibiting insulin‐like growth factor‐1 receptor and its downstream pathways

Abstract: Uveal melanoma (UM) has a high mortality rate due to liver metastasis. The insulin‐like growth factor‐1 receptor (IGF‐1R) is highly expressed in UM and has been shown to be associated with hepatic metastases. Targeting IGF signalling may be considered as a promising approach to inhibit the process of metastatic UM cells. Pristimerin (PRI) has been demonstrated to inhibit the growth of several cancer cells, but its role and underlying mechanisms in the IGF‐1‐induced UM cell proliferation are largely unknown. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This confirms previous observations in primary UM cell lines and UM samples [ 108 , 109 , 110 , 111 ] as well as in mUM [ 112 ]. Insulin-like growth factor-1 is a strong mitogen, which on stimulating IGF-1R signalling plays an important role in UM development and spread [ 113 ]. Hence, targeting IGF signalling has been considered a promising approach to inhibit the process of metastatic UM cells, e.g., recent studies have looked at this pathway using single [ 113 ] and a combinatory targeted approach [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…This confirms previous observations in primary UM cell lines and UM samples [ 108 , 109 , 110 , 111 ] as well as in mUM [ 112 ]. Insulin-like growth factor-1 is a strong mitogen, which on stimulating IGF-1R signalling plays an important role in UM development and spread [ 113 ]. Hence, targeting IGF signalling has been considered a promising approach to inhibit the process of metastatic UM cells, e.g., recent studies have looked at this pathway using single [ 113 ] and a combinatory targeted approach [ 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al have suggested that pristimerin inhibits IGF-1R/Akt/mTOR and ERK1/2 pathways and consequently leads to the loss of UM cell viability. They have also found that IGF-1 stimulates the expression of cyclin D1, which can be reversed by pristimerin to induce G1 phase arrest (23).…”
Section: Effects On Igf-1r: Regulating Downstream Pi3k/akt Erk/mapk Pathways and Resulting In G1 Phase Arrestmentioning
confidence: 96%
“…Emerging evidence has shown that pristimerin treatment gives rise to cell accumulation in G0/G1 phases and cell reduction in S and G2/M phases, indicating the induction of G0/G1 phase arrest to exhibit anti-proliferative effects on various cancers including CRC (22,38), breast cancer (9,21), uveal melanoma (UM) (18,23,30), chronic myelogenous leukemia (CML) (39), oral squamous cell carcinoma (OSCC) (27), esophageal cancer (40), pancreatic cancer (26,41), prostate cancer (24,25) and cholangiocarcinoma (42). However, a study related to the imatinib-resistant CML has found that pristimerin does not significantly affect the cell cycle other than the emergence of cells in the sub-G1 apoptotic phase (43).…”
Section: Alterations In Essential Cellular Events Under Pristimerin Treatment G1 Phase Arrest Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pristimerin, a natural triterpenoid compound, isolated from the traditional Chinese herbs Celastraceae and Hippocrateaceae , has shown numerous biological and pharmacological properties, such as anti-inflammatory ( Yadav et al, 2010 ), anti-oxidative ( Dos Santos et al, 2010 ; Hui et al, 2014 ), anti-tumor ( Li et al, 2019 ), anti-malarial ( Figueiredo et al, 1998 ) and anti-fungal effects ( Luo et al, 2005 ; Gullo et al, 2012 ). Many previous studies have confirmed that Pristimerin exerts its pharmacological effects through inactivating NF-κB and MAPK signaling ( Deeb et al, 2014 ; Yousef et al, 2018 ; Xie et al, 2019 ), which are similar pathways involved in osteoclastogenesis. However, the role of Pristimerin on osteoclastogenesis need further investigation.…”
Section: Introductionmentioning
confidence: 81%